Policies, programmes and research on adolescent and youth sexual and reproductive health in South Sudan: a systematic scoping review - Neha S Singh; Jessica Crawford; Chirrilo Madut; Chol Bak; Zack Wol (BMJ Open)
Objectives To provide an overview of research, policies and programmes related to the sexual and reproductive health (SRH) needs of adolescents and youth (AY) in South Sudan in order to identify the gaps and potential areas of focus for researchers, policymakers and local and global SRH actors.Design Systematic scoping review following the Joanna Briggs Institute criteria for evidence synthesis.Data sources Medline, Embase and Global Health were searched for articles dated between 9 July 2011 and 13 July 2023. A grey literature search was conducted using Google search engine and on the websites of key stakeholders.Eligibility criteria for selecting studies We included all types of studies, policies, reports and programmes that pertained to any aspect of the SRH AY (ages 10–35) in South Sudan.Data extraction and synthesis All articles were screened by the first author using the predetermined eligibility criteria. A secondary review was conducted on all selected articles to ensure alignment with criteria. Data were extracted from all eligible articles using an established data extraction tool. The authors identified overarching themes from the extracted data and results were synthesised based on those themes.Results We screened 728 articles, resulting in 52 articles included in the review (19 peer-reviewed, 33 grey literature). Results were mapped across South Sudan and synthesised by key AYSRH thematic areas. The results were largely focused on the experiences of adolescent girls and young women and the sociocultural norms and economic challenges that contribute to their lack of access to SRH services and increased risk of experiencing various forms of gender-based violence. Vulnerable populations were excluded from research, policies and programmes, including very young adolescents, LGBTQ youth and youth with disabilities.Conclusions Quality research has been done on AYSRH in South Sudan; however, there are many key areas that have not been addressed such as maternal mortality and morbidities, safe abortion and tailored interventions for specific subgroups. While some policies and programmes were identified that address AYSRH, robust programme evaluation processes or evidence of follow-through or implementation of government strategies are lacking.